2023
DOI: 10.3390/cancers15092407
|View full text |Cite
|
Sign up to set email alerts
|

Long Axial Field-of-View PET/CT Could Answer Unmet Needs in Gynecological Cancers

Abstract: Gynecological malignancies currently affect about 3.5 million women all over the world. Imaging of uterine, cervical, vaginal, ovarian, and vulvar cancer still presents several unmet needs when using conventional modalities such as ultrasound, computed tomography (CT), magnetic resonance, and standard positron emission tomography (PET)/CT. Some of the current diagnostic limitations are represented by differential diagnosis between inflammatory and cancerous findings, detection of peritoneal carcinomatosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 74 publications
0
0
1
Order By: Relevance
“…Moreover, increased [ 68 Ga]Ga-DOTA-TOC uptake in coronary arteries correlated with the global- and LAD- CACS. In this context, we report higher TBR compared to the previous report by Rominger et al (our TBR: 1.65 ± 0.53; Rominger et al: 1.21 ± 0.30);, which may reflect the noise reduction and increased sensitivity of a LAFOV PET system [ 9 , 10 , 26 , 34 ]. However, also differences in the clinical status of their patients may have impacted these results, and this may also explain why TBR in our study was generally lower than reported by Mojtahedi et al (2.04 ± 1.76).…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, increased [ 68 Ga]Ga-DOTA-TOC uptake in coronary arteries correlated with the global- and LAD- CACS. In this context, we report higher TBR compared to the previous report by Rominger et al (our TBR: 1.65 ± 0.53; Rominger et al: 1.21 ± 0.30);, which may reflect the noise reduction and increased sensitivity of a LAFOV PET system [ 9 , 10 , 26 , 34 ]. However, also differences in the clinical status of their patients may have impacted these results, and this may also explain why TBR in our study was generally lower than reported by Mojtahedi et al (2.04 ± 1.76).…”
Section: Discussioncontrasting
confidence: 58%
“…Detailed physical characterization, according to the NEMA NU 2-2018 standard, of both the uEXPLORER [21] and the Biograph Vision Quadra [22] also showed increased sensitivity. Thus, adjustment of the current clinical imaging protocols should be implemented, as has already been stated in various studies [23][24][25][26][27][28]. With the potential for improved radiation protection, lesion detection, and general work-flow efficiency, clinical performance requires proper evaluation.…”
Section: Introductionmentioning
confidence: 99%